Agile virtual enterprises implementation and management support - Cruz-Cunha, Maria Manuela, 1964-; Putnik, Goran, 1954-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"The authors address Agile/Virtual Enterprises as a new organizational paradigm, highly dynamic reconfigurable agile networks of independent enterprises sharing all resources, including knowledge, market, customers, etc., and using specific organizational architectures that introduce the enterprises' true virtual environments"--Provided by publisher.
Preface -- 1. Business requirements and background -- 2. A review on virtual enterprise models -- 3. BM_Virtual enterprise as an agile/virtual enterprise model -- 4. Requirements for agile/virtual enterprise integration -- 5. The proposal of a market of resources -- 6. Information and communication technologies : current developments -- 7. Traditional technologies to support agile/virtual enterprise -- 8. The organizational model for a market of resources -- 9. Development of the market of resources -- 10. Performance analysis -- 11. Market of resources : exploitation and future trends.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 18, 2010).
Keywords: Virtual reality in management; Business networks; Virtual corporations; Electronic books